Gagal Ginjal Kronik Yang Menjalani Terapi Hemodialisa Di RSUD dr ABDUL AZIZ - Nurhayati, Etiek; Kamilla, Laila; Lestari, cik Verra Budi (poltekkes kemenkes pontianak, 2023)
Hypertension is when a person experiences increased blood pressure on tissue and organ perfusion. One complication that can be caused by hypertension is kidney failure. Urea and creatinine are waste products of the body's metabolism. Ureum and creatinine levels will increase, indicating impaired kidney function. Damage that occurs to the kidneys must be treated one way with hemodialysis. The function of hemodialysis therapy is to reduce urea and creatinine levels in patients with chronic kidney failure.The study's general objective was to analyze urea and creatinine levels in hypertensive patients with chronic kidney failure undergoing hemodialysis therapy at dr. Abdul Aziz Singkawang General Hospital. The research design is analytically observational with a cross-sectional research design. Secondary data in this study were obtained from medical records and laboratory results of hypertensive patients with chronic kidney failure undergoing hemodialysis therapy without complications of DM, namely 37 respondents who performed urea and creatinine examinations before and after hemodialysis at dr. Abdul Aziz Singkawang by using a purposive sampling technique.The results of the study found 64 hypertensive patients undergoing hemodialysis and obtained a sample of 37 patients who met the criteria, namely hypertensive patients undergoing hemodialysis without complications of DM got an average urea level before hemodialysis 187.1919 mg/dl and after hemodialysis 136.0162 mg/dl. The intermediate creatinine level before hemodialysis was 14.0870 mg/dl and 11.0224 mg/dl after hemodialysis.The results of the Wilcoxon Signed Rank Test. They obtained p-value = 0.000 <α (0.05), which indicated differences in urea and creatinine levels before and after hemodialysis therapy in hypertensive patients with chronic kidney failure.